Edukasi DAGUSIBU untuk Penggunaan Obat Mata yang Aman di Klinik Pratama Nusantara Kesehatan - Fridelly Mairani; Grace Anastasia Br Ginting; Syukur Berkat Waruwu (Lembaga Pengembangan Kinerja Dosen, 2026)
Low public awareness of eye health and rational use of eye medications may increase the risk of eye disorders and infections. This community service activity aimed to improve public knowledge and awareness regarding the importance of maintaining eye health and applying the DAGUSIBU principle (Get, Use, Store, and Dispose of medicines properly) in the use of eye drops. The activity was conducted at the Klinik Pratama Nusantara Kesehatan through interactive counseling, demonstrations of proper eye drop administration techniques, and education on the prevention of common eye disorders and the role of healthcare professionals. Pre-test and post-test evaluations showed a significant increase of approximately 35% in participants’ knowledge regarding eye hygiene and correct eye medication use. This educational program is expected to contribute to long-term improvements in rational eye medication use, reduce the risk of misuse, and serve as a model for sustainable eye health education in a primary healthcare settings.